The credibility of citizen journalists / Nur Hasliza Mohamad…[et.al] - Mohamad, Nur Hasliza; Mohd Fuad, Nurul Aida; Azhar, Nurul Aqilah; Mohd Zawawi, Nur Syazana; Nik Azaham, Nik Nur Jasmine (Faculty of Communication and Media Studies, 2016)
In these modern days, the public tend to get news and issues, as the sophisticated gadgets have been created. All of the information could easily get only by browsing in the social media. All of the news and issues that have been spread through the social media written by the citizen journalists, this days. Hence, publics accepted those news and issues without validity. Citizen journalists tend to write news and issues without seeking its validity sources and the society tend to believe the news. The purpose of doing this research is to study the credibility of citizen journalists and in the same time researches study the way that must be taken by citizen journalists before writing and posting the news or current issues. The methods that have been used were by interview several informants such as lecturers and media influencers for answering the research objectives. From this research, researchers found that citizen journalists in social media can attract the trustworthiness of publics but it is actually depends on how an individual itself receive the news.